Ammonia Decomposition at Titanium Oxide Nanotube Photosensitive Anode - Yong X. Gan; Jeffrey Zampell; Ryan N. Gan; Juan C. Miranda; Marla Lopez; Andrew Vitaljic; Bruce Y. Decker; James L. Smith; Jimmie C. Oxley (Archives of Current Research International, 2014)
Kinetic behavior of ammonia decomposition at titanium dioxide nanotube photosensitive anode was studied. Ammonia was dissolved into water to form solutions with difference concentrations. The ammonia concentration ranges from 0.025 wt% to 10 wt%. Time-dependent open-circuit potential was measured to examine the photochemical response of the cell. The ammonia decomposition behavior was confirmed by measuring the decrease in pH values of the solutions. In addition, the kinetic behavior of ammonia decomposition was characterized under the actions of both ultra violet light irradiation and polarization. The current density values at the titanium dioxide nanotube anode during anodic polarization and UV light irradiation tests were used to compare the ammonia decomposition rates associated with photon excitation and polarization. The double–layer capacitance was estimated as high as 35 F/m2 indicating the excellent charge storing capability of the nanotube photosensitive anode. The effect of ammonia concentration on the open-circuit potential was also observed. In the lower ammonia concentration range, the change in the open circuit potential increase with the increasing in the ammonia concentration. Interestingly, in the higher concentration range from 2.5 wt% to 10 wt%, the change in the open circuit potential reveals a reversed trend.